2015
DOI: 10.4238/2015.june.9.1
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor FokI gene polymorphism and tuberculosis susceptibility: a meta-analysis

Abstract: ABSTRACT. Numerous studies have evaluated the association between FokI polymorphisms in the vitamin D receptor (VDR) gene and tuberculosis risk. However, the spe cific association remains controversial. In this study, we performed a meta-analysis to assess the association between the VDR gene FokI polymorphism and tuberculosis. Published studies from the PubMed and Embase databases were retrieved. The pooled odds ratio (OR) with 95% confidence interval (CI) was calculated using fixed-or random-effect models. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…Moderate heterogeneity was found in this study. However, heterogeneity was significantly reduced compared with previous meta-analyses [ 20 , 21 ]. These results not only could confirm HIV infection status as the main source of heterogeneity in previous meta-analyses, but are also the reason why we conducted this study.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Moderate heterogeneity was found in this study. However, heterogeneity was significantly reduced compared with previous meta-analyses [ 20 , 21 ]. These results not only could confirm HIV infection status as the main source of heterogeneity in previous meta-analyses, but are also the reason why we conducted this study.…”
Section: Discussionmentioning
confidence: 62%
“…However, previous literature about the associations between Fok I polymorphism and the risk of TB has provided inconsistent results [ 6 19 ]. A previous meta-analysis found that Fok I polymorphism was associated with TB risk with significant heterogeneity [ 20 , 21 ]. However, they did not stratify by HIV status.…”
Section: Introductionmentioning
confidence: 99%
“…Gp91phox, encoded by CYBB ranked second in Table 1, is an essential subunit of NADPH oxidase complex. Alterations in macrophage function, such as defects in NADPH oxidase30 and the vitamin D receptor,31 are known as risk factors for mycobacterial infection. Several studies have shown that mutations in CYBB could result in X-linked chronic granulomatous disease with much higher risk of TB,32–34 which is an immunodeficiency caused by defective activity of NADPH oxidase in phagocytes 33,35.…”
Section: Resultsmentioning
confidence: 99%
“…The authors showed that African-American individuals with high susceptibility to TB had low serum 25-hydroxyvitamin D levels, leading to inefficient cathelicidin mRNA expression (Liu et al, 2006). Several VDR polymorphisms (FokI, TaqI, BsmI, ApaI) have been found to be associated with TB resistance (Uitterlinden et al, 2004;Sun et al, 2015). A Gambian study has demonstrated that the homozygous T/T TaqI genotype, correlated with higher circulating levels of 1,25(OH) 2 D 3, might be protective against TB (Bellamy et al, 1999).…”
Section: Vitamin D Receptor (Vdr)mentioning
confidence: 99%